Fuelwood revisited: what has changed in the last decade? - Center for International Forestry Research (Center for International Forestry Research, 2003)
This infobrief provides key points that the available evidence does not substantiate earlier concerns that woodfuel demand has been outpacing sustainable supply on a scale that makes it a major cause of deforestation. The balance between demand and supply is seldom an issue requiring forestry intervention on a national scale. However, the rapid rise in charcoal production and its concentration, to supply large urban markets, certainly warrants further investigation. Annual global consumption of fuelwood appears to have peaked in the mid-1990s, at about 1600 million m3 and is now believed to be slowly declining. However, global charcoal consumption is growing rapidly (and at the turn of the century, was estimated to be using roughly 270 million m3 of wood pa). The combined aggregate is still rising but at a declining rate and substantially less rapidly than the equivalent growth in population. Overall, the total quantities of woodfuels being used are still huge, with an estimated 2.4 billion people currently utilising wood and other forms of biomass.